Teacher Leadership and School/System Change: Exploring the Contemporary Evidence - Harris, Alma; Jones, Michelle; Ismail, Nashwa (International Journal of Education Policy and Leadership, 2025)
This article presents the findings from a review of contemporary scholarly work on teacher leadership, with a focus on the international evidence concerning the relationship between teacher leadership and school/system change. The PRISMA approach (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was applied to review contemporary scholarly evidence over ten years, resulting in the identification of 26 journal articles that fully met the inclusion and exclusion criteria set for the review. The findings from this review suggest that, under the right conditions, teacher leadership can contribute to the process of school and system change. This review also highlights the need for more consolidated empirical work on the impact and outcomes of teacher leadership.